Evaluating Four Factors of Students’ Engagement in Task-based Learning under Blended English Learning Environment Using PLS-SEM Approach (International Journal of Language, Literacy and Translation, 2024)
The discussion in this article centres on the implementation of blended learning and the learning duties that are delegated to students within a blended learning environment. Learners will be entrusted with blended learning duties in the midst of pandemics. However, the efficacy of task utilisation may fail to fulfil its intended objective. Therefore, the research presented in this article assessed the perceived level of student engagement in integrated learning tasks based on the following criteria: task timeliness, task richness, task accuracy, and task adaptability. The investigation was carried out at four universities located in Shandong Province, China. An English course was conducted in the spring of 2022 employing a task-based teaching approach and a combination of traditional and online instructional design. The instructors allocated learning tasks for each class, both in-person and online. Specifically, the students were given these tasks prior to, during, and subsequent to each class. The duties completed by the students were assessed and the instructors provided feedback. At the conclusion of the academic term, students were requested to provide feedback through the administration of a questionnaire. The study’s findings underscored the students’ favourable disposition towards assignments within integrated learning courses. The research emphasised the importance of meticulously crafted assignments that possess the qualities of promptness, depth, precision, and flexibility. Moreover, the efficacy of integrated learning is enhanced by practical assessment methods that gauge students’ attributes and provide timely feedback on task completion. Additionally, learner autonomy and student engagement are enhanced by the task-based blended learning course.